Meningkatkan Kemampuan Membaca Grafik melalui media Ping-pong Ball Chart pada Anak Usia Dini di Era Pandemi - Niken Ayu Nila Ariani; Naili Rohmah (JURNAL LENTERA ANAK, 2022)
During the pandemic, with the elimination of face-to-face learning, children become less knowledgeable. More about learning graphic concepts. The purpose of this research is to improve the ability to read charts in early childhood in the pandemic era using the Ping-pong Ball Chart media. This research uses descriptive qualitative method. Data collection methods used are interviews, observation, and documentation because they can describe the situation accurately. Based on the results of the study, on the first day there was no change in the child's ability to read graphs. Where child not reads according to what he sees. there are children who are not at all able to conclude what he sees. In the learning process on the second and third day after the teacher conducted learning using the Ping-pong Ball Chart media, the children had experienced an increase in reading graphs, there were 4 students who drastically increased their ability to read graphs.